Modeling of Liquids Behavior: Experiments, Theory and Simulations - Acree, Jr; Saavedra, Juan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Physical and chemical properties of simple and complex liquids or mixtures play an important role in industrial manufacturing processes. Liquids serve as the reaction solvent media in the preparation of new chemical compounds, as an extraction solvent in the purification of synthesized materials, as a solubilizing agent in both pharmaceutical formulations and personal healthcare products, as a fuel to meet industrial heat demand, and as a coolant to maintain a desired reaction temperature. Special emphasis was given to studies that reported the latest technical and theoretical results concerning the properties and processes of industrial significance. This Special Issue reports new experimental data for select liquid mixtures, and discusses modern experimental and computational methods for measuring and predicting thermophysical properties and phase equilibria. Each paper provides valuable insight into the underlying fundamental principles that govern the studied processes. The predictive expressions and models presented in the published papers will enable practicing scientists and engineers to estimate physical and thermodynamic properties needed in industrial process design calculations. This Special Issue has constituted an international forum for various groups of researchers to summarize their most recent developments and ideas applied to the liquid state.